2016
DOI: 10.1007/s00167-016-4341-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased revision rate with posterior tibial tunnel placement after using the 70-degree tibial guide in ACL reconstruction

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Among the most common are participation in high-level sports, 6,14,41,45 younger age, 30,42,45 and technical issues related to the surgery. 5,18,30,32 Several possible explanations for the residual knee laxity and risk of revision surgery after ACLR were seen in the current study. We found a nonsignificant tendency (P = .08) that athletes undergoing revision surgery were younger at the primary surgery (median, 20.5 years; n = 14) than the group not in need of revision surgery (median, 24 years; n = 135).…”
Section: Discussionmentioning
confidence: 69%
“…Among the most common are participation in high-level sports, 6,14,41,45 younger age, 30,42,45 and technical issues related to the surgery. 5,18,30,32 Several possible explanations for the residual knee laxity and risk of revision surgery after ACLR were seen in the current study. We found a nonsignificant tendency (P = .08) that athletes undergoing revision surgery were younger at the primary surgery (median, 20.5 years; n = 14) than the group not in need of revision surgery (median, 24 years; n = 135).…”
Section: Discussionmentioning
confidence: 69%
“…In the current study, it was found that the tibial location significantly affected the mean anisometry. In the recent study by Inderhaug et al 32 it was shown that posterior tibial socket positioning was related to an increased rate of revision cases. Future studies may further explore the effect and its significance of the tibial socket positioning.…”
Section: Discussionmentioning
confidence: 96%
“…Inaccurate tunnel placement was found to predict ACLR failure in three studies [17][18][19], and it was an important cause of early graft failure, accounting for 60-79 % of failure cases [17]. Positioning errors in tunnel placement can involve the femoral tunnel and the tibial tunnel, which may lead to excessive graft forces and strain as well as graft impingement, and eventually result in persistent in-stability and loss of motion [79,80].…”
Section: Tunnel Placementmentioning
confidence: 99%